Clinicopathological Analysis of Hysterectomy Specimens - Dr. Ashwini Kolur; Dr. Shreya S Desai; Dr. Sneha Reddy R; Dr. Sahana Nayak (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: The uterus is vital reproductive organ prone to develop several non-neoplastic and neoplastic lesions in womancontributing significantly to increased morbidity and mortality. Although many treatment options are available, hysterectomy isstill widely used treatment modality worldwide.Objectives: The study was proposed to analyse the patterns of lesions in hysterectomy specimens and to analyse the clinico-pathological correlation in hysterectomy specimen.Methods: A 6-monthretrospective study was performed in Department of Pathology, Karwar institute of Medicalscience, Karwar. Baseline data were collected from inpatient files and histopathology reports were collected from Department of Pathology,to identify the most common pathologies in hysterectomy specimens.Results:78 hysterectomy cases were analysed and the peak age group were from 35-45 years (42.30%), and the most common clinical presentation was fibroids (42.30%). Most common histopathological lesion was leiomyoma 37 cases (47.4%), followed by 16 cases (12.82%) presented as adenomyosis, and 14 cases (10.26%) had dual pathology of both leiomyoma and adenomyosis. The commonest incidental histopathological finding seen in hysterectomy specimens was chronic cervicitis.Conclusions: Hysterectomy is the most commonly performed elective major gynaecological surgery. Though the histopathological analysis correlates well with the clinical diagnoses, quite a few lesions like chronic cervicitis and adenomyosis were encountered as pure incidental findings. Hence, it is mandatory that every hysterectomy specimen, even if it grossly appears to be normal, should be subjected to detailed histopathological examination for confirming diagnosis and better postoperative management